Social Non-profit Bioentrepreneurship: Current Status and Future Impact on Global Health - Sadeghi, Amir H.; Koldeweij, Charlotte; Trujillo-de Santiago, Grissel; Tannazi, Milad; Hosseinnia, Nikkie; Loosbroek, Oscar van; Manbachi, Amir; Taverne, Yannick J. H. J.; Bogers, Ad J. J. C.; Alvarez, Mario Moisés (Frontiers in Public Health, 2021)
For-profit biotechnological and pharmaceutical companies have played an essential role in the research and development (R&D) of innovative medical products and drugs for many decades and embody a trillion-dollar industry. The past decades have been marked by an increase in growth of social non-profit biotechnology companies and organizations led by entrepreneurs committed to solve (global) health issues. In this review, we define the concept of social bioentrepreneurship and consider the potential impact of such ventures on global health. We analyse the current status of non-profit biotechnology and clarify the strategy, motivation, funding, and marketing techniques of these enterprises. We find that these non-profit ventures mainly focus on neglected and rare diseases by using different but also similar funding, marketing, and business strategy approaches to for-profit biotechnology enterprises. We also identify good leadership, multidisciplinary teams, and public awareness as key components to achieve long-term survival and higher success rates. Challenges faced by bioentrepreneurs include the lack of a clearly defined regulatory environment or governmental incentives to support their endeavors. Overall, with this qualitative data review and market analysis we draw a promising picture of social non-profit bioentrepreneurship and underscore its current and future impact on global health issues.